Stock liquidity and stock returns: the moderating role of financial constraints - Veronika Daniar Febrianti; Siti Saadah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study aims to analyze the effect of stock liquidity on stock returns in large and small capitalization companies and the moderating role of financial constraints in the relationship. Design/Methodology/Approach: In this study, panel data analysis was conducted on 113 manufacturing sector companies on the Indonesia Stock Exchange from 2015 to 2019, grouped into small and large capitalization companies. To avoid measurement errors from applying the KZ index, which is very likely to occur, this study used the upper quartile (Q3) of the Debt-to-Equity Ratio (DER) and a dummy variable as an artificial variable to measure financial constraints instead of the KZ index.Research findings: The results highlighted that liquidity is a predictor that could significantly explain the movement of stock returns in this sector. Investors, thus, will require additional compensation in the form of higher returns for holding less liquid stock. The study also found a significant moderating role of financial constraints. Consequently, as the illiquidity of stocks increases, additional greater compensation will be requested by investors on the stocks of companies experiencing financial constraints.Theoretical contribution/Originality: This study provides additional empirical evidence for the studies documented that investors will ask for additional return compensation for stocks with low liquidity, and investors will demand higher additional returns in companies experiencing financial constraints. This finding indicates that liquidity is essential in risk premium forming stock returns.Practitioner/Policy implication: This study can be used for investors or traders when choosing an investment strategy to be carried out.